Optimization of Drilling Well Design: A Review - Khudhair, Saif; Al-Mahdawi, Faleh H. M. (Iraqi Journal of Chemical and Petroleum Engineering, 2022)
Drilling well design optimization reduces total Authorization for Expenditures (AFE) by decreasing well constructing time and expense. Well design is not a constant pattern during the life cycle of the field. It should be optimized by continuous improvements for all aspects of redesigning the well depending on the actual field conditions and problems. The core objective of this study is to deliver a general review of the well design optimization processes and the available studies and applications to employ the well design optimization to solve problems encountered with well design so that cost effectiveness and perfect drilling well performance are achievable. Well design optimization processes include unconventional design(slimhole) compared with fat design, in addition to optimizing casing setting depth selection and casing string loads. Finally, we demonstrate well trajectory design considerations and optimization. The optimization process that mentioned above is significantly reduce drilling cost and time since, slimhole design with smaller casing and hole size reduce mud volume cost, steel cost and pump fuel cost. Optimum casing seat selection can ovoid serious problem such as kick and losses that increase nonproductive time (NPT) if kick tolerance and downhole pressure profile is not considered. Anticipating optimum stress loads in casing design is most effective way to reduce casing strings cost avoiding additional cost for designing with useless worst conditions. Wellbore trajectory optimization with geomechnic consideration is major concern to reduce the problem encountered with high torque, drag, formation collapse that result stuck pipe and non-productive time (NPT).